The Influence of E-Service Quality and Product Quality on Zalora Fashion Product Purchase Decisions Mediated by E-Trust - Cahaya, Yohanes Ferry; Purnomo, Lucky Bayu; Pujiati, Herni; Yosepha, Sri Yanthy; Aminah, Siti (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This study examines the impact of E-Service Quality and Product Quality on Purchase Decision for fashion products on the Zalora platform, with E-Trust serving as a mediating variable. Using a quantitative approach, the analysis employs Structural Equation Modeling–Partial Least Square (SEM-PLS). Data were collected via surveys from 295 active Zalora users in Indonesia. The results indicate that both E-Service Quality and Product Quality significantly influence E-Trust, which in turn significantly affects Purchase Decision. Additionally, E-Service Quality directly and significantly impacts Purchase Decision, whereas the direct effect of Product Quality on Purchase Decision is not significant. These findings suggest that electronic trust (E-Trust) mediates the relationship between electronic service quality and product quality on purchase decisions. The study recommends that fashion e-commerce managers like Zalora prioritize enhancing digital service quality and consistently build customer trust, as trust plays a crucial role in driving purchase decisions. The practical implications of this research can guide marketing strategies and digital service development in the fashion e-commerce industry.